Longevity trend in Germany - Matthias Reitzner (European Actuarial Journal, 2023)
In Germany, a trend for decreasing mortality probabilities has been observed in the last 50~years, yielding an increasing life expectancy. The German Actuarial Association DAV offers a standard method for modeling this longevity trend in calculations concerning life insurance by using the life table DAV 2004R. In this note it is investigated, whether or to which extent the longevity function of the DAV 2004R can be used for calculating the expected total number of deaths in Germany.
Keywords: 510; Life tables; Longevity factors; Mortality decrease; Expected number of deaths